Activating hypoxia inducible factor in the heart by genetic inactivation of von Hippel Lindau protein reduces myocardial infarct size. (22nd September 2015) - Lim, S; Ong, SG; Shukla, DH; Maxwell, P; Hausenloy, DJ; Yellon, DM
Abstract : Introduction: The activation of hypoxia inducible factor 1 (HIF-1) has been demonstrated to be cardioprotective. Under normoxic conditions von Hippel Lindau (VHL) protein assists in the degradation of HIF-1. We hypothesised that the activation of HIF-1 within the heart by the genetic inactivation of cardiac-specific VHL reduces myocardial infarct size. Methods: We used conditional cardiac-specific VHL knockout mice that express an inducible Cre recombinase transgene to delete the VHL-floxed gene within the heart in an acute manner following tamoxifen induction (4 mg/mouse per day for 5 days by intraperitoneal injection). Conditional cardiac-specific VHL knockout mice and littermate controls were then subjected to in-situ 30 minutes left anterior coronary artery ischaemia followed by 120 minutes of myocardial reperfusion, at the end of which myocardial infarct size was determined by tetrazolium staining. Results: Using immunostaining techniques, the cardiac-specific ablation of VHL was demonstrated to activate myocardial HIF-1 markedly when compared with control hearts in which no HIF-1 activation was observed. The activation of myocardial HIF-1 arising from the genetic inactivation of VHL resulted in a smaller myocardial infarct size when compared with control (30.8 ± 8.3% in VHL knockout versus 62.7 ± 4.1% in control; p<0.05; N = 5–6 animals per group). Conclusion: The acute activation of the HIF-1 within the heart from the genetic inactivation of cardiac-specific VHL reduces myocardial infarct size.